The Success Paradox : Why We Need a Holistic Theory of Social Mobility - Atherton, Graeme (Book collections on Project MUSE., 2017)
Social mobility needs a re-boot. The narrow, economistic way of measuring it favoured by politicians and academics is unsustainable and is contributing to rising inequality. This timely book provides an alternative, original vision of social mobility and a route-map to achieving it. It examines how the term 'social mobility' structures what success means and the impact that has on society. Providing a new holistic approach that encompasses education, the economy and politics, Atherton recasts the relationship with employers, embracing radical opportunities provided by technology and rethinking what higher education means. He also goes beyond employment to incorporate progress in non-work areas of life. Based on the need to improve well-being, not just income or occupation, the book addresses one of the key issues facing 21st century society in a new way and provides valuable insights for policymakers and academics.--Publisher website.